The responsibility of intellectuals : reflections by Noam Chomsky and others after 50 years - Allott, Nicholas; Knight, Chris, 1942-; Smith, N. V. (Neilson Voyne) (Online access: OAPEN Open Research Library (ORL), 2019)
'The Responsibility of Intellectuals' propelled Noam Chomsky onto the US political scene half a century ago. This book revisits the seminal work, and features six new essays written to celebrate and explore its relevance in today's world, including Chomsky's recollections of the background to the original publication, and extensive commentary.